Adverse effects of daily oral pre-exposure prophylaxis in men who have sex with men and transgender women: a systematic review and meta-analysis - Marcos Pereira; Caroline Tianeze de Castro; Laio Magno; Tarcio de Almeida Oliveira; Fabiane Soares Gomes; Fabiane Maria Fernandes Neves; Pedro Rafael dos Santos do Nascimento; Ines Dourado (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
Abstract: The adverse effects of oral pre-exposure prophylaxis (PrEP) using tenofovir disoproxil fumarate are barriers to PrEP initiation and continuation. Although serious effects are rare and predictable, evidence for this assessment among men who have sex with men (MSM) and transgender women (TGW) is still limited. This study assesses the adverse effects of daily oral PrEP in MSM and TGW. This is a systematic review and meta-analysis of clinical trials and cohort studies on the use of daily oral PrEP selected from the PubMed/MEDLINE, Embase, LILACS, and Cochrane CENTRAL databases. Data extraction included adverse effects and changes in renal and hepatic markers. Random effects models were used to summarize the risk of adverse effects throughout the study. Heterogeneity was assessed using the Cochran's Q test and the inconsistency test (I2). The risk of bias and the certainty of the evidence were assessed using the Cochrane Collaboration recommendations. The search identified 653 references. Of these, 10 were selected. All studies assessed the eligibility of renal and hepatic markers. The use of daily oral PrEP was not associated with grade 3 or 4 adverse events (RR = 0.99; 95%CI: 0.83-1.18; I2 = 26.1%), any serious adverse event (RR = 1.04; 95%CI: 0.58-1.87; I2 = 88.4%), grade 3+4 creatinine level (RR = 0.66; 95%CI: 0.24-1.84; I2 = 79.9%), and grade 3 or 4 hypophosphatemia (RR = 0.56; 95%CI: 0.15-2.10). The certainty of the evidence ranged from high to moderate for the outcomes analyzed. Daily oral PrEP is safe and well tolerated by MSM and TGW. Adverse effects were minimal and evenly distributed between intervention and control.